Menara Tabung Haji Tun Razak, Kuala Lumpur - Khairul Azuhar, Muhammad Hakimi Haikal; Kamal Ariffin, Mujahid; Kamaruddin, Muhammad Na’im; Soddri, Muhamad Hasif (2024)
The Menara Tabung Haji Tun Razak building in Kuala Lumpur is the subject of this study. The building and the maintenance method that was employed there are the subjects of this report. All of the data gathered from our site visit at Menara Tabung Haji Tun Razak and our interviews with project managers are included in this report. Menara Tabung Haji Tun Razak mostly uses services that are comparable to those of other typical office buildings. However, Menara Tabung Haji Tun Razak is unique in that it is a certified green building. This building used TH Universal Builders, their in-house maintenance management company. They were responsible for managing both in-house and external building upkeep. Considering that Menara Tabung Haji Tun Razak is a new building, overall upkeep is still in good condition. However, they still need to make improvements to their maintenance plans.